A re-examination of constrained Pareto inefficiency in economies with incomplete markets - Concetta Mendolicchio; Tito Pietra (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
We establish that, when the number of agents is sufficiently large, but finite, there are open sets of economies with constrained Pareto inefficient equilibria, and provide a simple sufficient condition for CP inefficiency. We also show that there are open sets of economies with CPO equilibria. – – Wir zeigen, dass, wenn die Zahl der Agenten ausreichend groß, aber endlich ist, offene Sets an Ökonomien mit eingeschränkter Paret-Effizienz (CP) existieren und bieten eine einfache hinreichende Bedingung für CP-Ineffizienz. Wir zeigen auch, dass offene Sets an Ökonomien mit CPO-Gleichgewichten existieren.
Keywords: D51; D52; 330; GEI; constrained Pareto inefficiency; numeraire assets